Intensity, Duration, and Location of High-Definition Transcranial Direct Current Stimulation for Tinnitus Relief. (May 2016) - Shekhawat, Giriraj Singh; Sundram, Frederick; Bikson, Marom; Truong, Dennis; De Ridder, Dirk; Stinear, Cathy M.; Welch, David; Searchfield, Grant D.
Background and Objective . Tinnitus is the perception of a phantom sound. The aim of this study was to compare current intensity (center anode 1 mA and 2 mA), duration (10 minutes and 20 minutes), and location (left temporoparietal area [LTA] and dorsolateral prefrontal cortex [DLPFC]) using 4 × 1 high-definition transcranial direct current stimulation (HD-tDCS) for tinnitus reduction. Methods . Twenty-seven participants with chronic tinnitus (>2 years) and mean age of 53.5 years underwent 2 sessions of HD-tDCS of the LTA and DLPFC in a randomized order with a 1 week gap between site of stimulation. During each session, a combination of 4 different settings were used in increasing dose (1 mA, 10 minutes; 1 mA, 20 minutes; 2 mA, 10 minutes; and 2 mA, 20 minutes). The impact of different settings on tinnitus loudness and annoyance was documented. Results . Twenty-one participants (77.78%) reported a minimum of 1 point reduction on tinnitus loudness or annoyance scales. There were significant changes in loudness and annoyance for duration of stimulation, F (1, 26) = 10.08, P < .005, and current intensity, F (1, 26) = 14.24, P = .001. There was no interaction between the location, intensity, and duration of stimulation. Higher intensity (2 mA) and longer duration (20 minutes) of stimulation were more effective. Conclusions . A current intensity of 2 mA for 20-minute duration was the most effective setting used for tinnitus relief. The stimulation of the LTA and DLPFC were equally effective for suppressing tinnitus loudness and annoyance.